Federal perceptions and tribal sovereignty: consultation and relations between the Bureau of Land Management and federally recognized tribes - Lundy, Morgan, author; Hausermann, Heidi, advisor; Henry, Edward, committee member; Schneider, Lindsey, committee member (Colorado State University. Libraries, 2022)
The Bureau of Land Management (BLM) is an institution of settler colonialism. Its origins lie in Western expansion and the dispossession of land from Indigenous communities. Today it administers the largest collection of public lands in the country and must maintain relationships through consultation with Tribal governments. Even though these relationships are legally mandated, there is often contention and confusion surrounding them. Despite these issues, there is little research looking at how the BLM understands and carries out Tribal relations. Using semi-structured interviews with BLM employees and decisionmakers, Part I of this research analyzes how individual actors understand and shape these government-to-government relationships. Results indicate that even though BLM decisionmakers are responsible for Tribal relations, archaeologists are the primary employees maintaining them. Part II evaluates how these same actors understand and account for Tribal sovereignty in their work. Findings highlight that Tribal sovereignty is not a static concept and is negotiated in these government-to-government relationships. This thesis does not provide recommendations for improving the BLM's Tribal relations. Instead, it demonstrates how BLM staff members manipulate and move within settler colonial structures. Hopefully, this research provides basic information useful in dismantling and reforming settler colonial institutions that have historically oppressed Native nations and communities.